2016
DOI: 10.1172/jci.insight.88178
|View full text |Cite
|
Sign up to set email alerts
|

Bladder catheterization increases susceptibility to infection that can be prevented by prophylactic antibiotic treatment

Abstract: International audienceCatheter-associated urinary tract infections (CAUTI) are the most common hospital-associated infections. Here, we report that bladder catheterization initiated a persistent sterile inflammatory reaction within minutes of catheter implantation. Catheterization resulted in increased expression of genes associated with defense responses and cellular migration, with ensuing rapid and sustained innate immune cell infiltration into the bladder. Catheterization also resulted in hypersensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 49 publications
(60 reference statements)
3
34
0
Order By: Relevance
“…The enrichment of GO terms associated with immune function within down-regulated genes during co-infection in the presence E. faecalis suggested that we might also observe differential gene expression specifically in genes associated with the cell populations responding to CAUTI [19]. To test this, we examined the Immunological Genome Project (ImmGen) database, which comprises publicly available data from a collection of immune cell types in C57BL/6J mice [13, 26].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The enrichment of GO terms associated with immune function within down-regulated genes during co-infection in the presence E. faecalis suggested that we might also observe differential gene expression specifically in genes associated with the cell populations responding to CAUTI [19]. To test this, we examined the Immunological Genome Project (ImmGen) database, which comprises publicly available data from a collection of immune cell types in C57BL/6J mice [13, 26].…”
Section: Resultsmentioning
confidence: 99%
“…After 24 hours, whole bladders were removed and incubated overnight in RNAlater (Qiagen) to allow complete tissue penetration by the protectant prior to storage at −80°C. RNA was extracted as described [60]. For each sample condition, a total of three sequencing libraries were constructed from 50-200 ng of rRNA-depleted RNA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bladder catheterization itself was reported to cause sterile inflammation in a murine model, with CD 45+ neutrophils as the main infiltrating immune cells. Using this model, E. coli and E. faecalis infections were shown to cause urothelial barrier disruption and further immune cell infiltration (27). Pyuria is known to occur in patients with indwelling catheters independent of the symptomology (7).…”
Section: Introductionmentioning
confidence: 99%